Propagation of Pacemaker Activity and Peristaltic Contractions in the Mouse Renal Pelvis Rely on Ca2+-activated Cl− Channels and T-Type Ca2+ Channels. Issue 6 (24th August 2022) - Grainger, Nathan; Shonnard, Cameron C; Quiggle, Sage K; Fox, Emily B; Presley, Hannah; Daugherty, Robbie; Shonnard, Matthew C; Drumm, Bernard T; Sanders, Kenton M
Abstract: The process of urine removal from the kidney occurs via the renal pelvis (RP). The RP demarcates the beginning of the upper urinary tract and is endowed with smooth muscle cells. Along the RP, organized contraction of smooth muscle cells generates the force required to move urine boluses toward the ureters and bladder. This process is mediated by specialized pacemaker cells that are highly expressed in the proximal RP that generate spontaneous rhythmic electrical activity to drive smooth muscle depolarization. The mechanisms by which peristaltic contractions propagate from the proximal to distal RP are not fully understood. In this study, we utilized a transgenic mouse that expresses the genetically encoded Ca 2+ indicator, GCaMP3, under a myosin heavy chain promotor to visualize spreading peristaltic contractions in high spatial detail. Using this approach, we discovered variable effects of L-type Ca 2+ channel antagonists on contraction parameters. Inhibition of T-type Ca 2+ channels reduced the frequency and propagation distance of contractions. Similarly, antagonizing Ca 2+ -activated Cl − channels or altering the transmembrane Cl − gradient decreased contractile frequency and significantly inhibited peristaltic propagation. These data suggest that voltage-gated Ca 2+ channels are important determinants of contraction initiation and maintain the fidelity of peristalsis as the spreading contraction moves further toward the ureter. Recruitment of Ca 2+ -activated Cl − channels, likely Anoctamin-1, and T-type Ca 2+ channels are required for efficiently conducting the depolarizing current throughout the length of the RP. These mechanisms are necessary for the efficient removal of urine from the kidney. Graphical Abstract: